Family Knowledge on Pulmonary Tuberculosis in Pediatric Polyclinic, Makassar Community Lung Health Center - Azzahra, Nur Azizah; Widyanti, Trisna; Kamilah, Ummu; Hilintang, Rendhar Putri; Putri, Amilah Eka; Bonita, A. Ferina Herbourina (Universitas Pahlawan Tuanku Tambusai, 2025)
The highest number of pediatric tuberculosis (TB) cases in South Sulawesi in 2016 was in Makassar. Many pediatric tuberculosis cases in Makassar were treated at the Makassar Community Lung Health Center. This study aims to describe the knowledge of families of TB patients about the prevention of pulmonary TB at the Pediatric Polyclinic, Makassar Community Lung Health Center. This study is quantitative with a descriptive approach. The sample consisted of 31 respondents selected through a purposive sampling method. The respondents were families of pediatric TB patients. Data analysis was conducted using univariate analysis with SPSS. The results of the study showed that the majority of respondents knew that pulmonary tuberculosis is a contagious disease (45.2%), the source of respondents’ information came from doctors (96.8%), the cause of pulmonary tuberculosis was due to transmission from pulmonary TB patients (29.0%), pulmonary tuberculosis transmission occurs through the air (35.5%), transmission prevention by patients is done by using masks (48.4%), the symptom of pulmonary tuberculosis in children is prolonged cough (74.2%), the prevention of pulmonary TB in children is by avoiding cigarette smoke (32.3%), good home environment conditions for preventing transmission are cleanliness (77.4%), the place for sputum disposal is in the toilet (38.7%), and the cough etiquette for pulmonary TB patients is using a mask (58.1%). The study concludes that most respondents have good knowledge about pulmonary tuberculosis, mainly because almost all of them reported that their source of information was from doctors.